THE DISTRIBUTION OF THE GALAXY NONTHERMAL RADIO EMISSION SPECTRAL INDEX AT DECAMETER WAVELENGTHS - Vasilenko, N. M. (Одеські астрономічні публікації, 2007)
A spatial distribution map for the background spectral index of the decameter radio-wave emission from the Northern sky is presented. The spectral index was determined by using radio surveys obtained with the UTR-2 radio telescope for 14.7, 16.7, 20, and 25 MHz. The temperature spectral index β(Tv ≈ v-β ) was calculated for all pairs of the above frequencies and then averaged. The contributions from the point and extended Galactic sources were removed from β with the a low-pass FIR filter. The spectral index distribution includes the continuous galactic and the isotropic extragalactic components. The spectral index averaged over the entire investigated part of the sky is ≈ 2.43. For a rather large region with high galactic latitudes (b > 30º), the spectral index flattens to become ≈ 2.24. The map clearly reveals regions with increased values of the spectral index (β ≈ 2,6 - 2.8); they correspond to parts of Loop I and Loop III.